The influence of hamstring autograft size on patient reported outcomes and risk of revision following anterior cruciate ligament reconstruction: A MOON cohort study - Mariscalco, Michael W. (2013)
PURPOSE: The purpose of this study is to evaluate the effect of graft size on patient-reported outcomes and revision risk following ACL reconstruction. METHODS: A retrospective chart review of prospectively collected cohort data, 263 of 320 consecutive patients (82.2%) undergoing primary ACL reconstruction with hamstring autograft were evaluated. Graft size, femoral tunnel drilling technique, patient age, sex, and BMI at the time of ACL reconstruction, pre-operative and 2-year post-operative KOOS and IKDC scores, and whether each patient underwent revision ACL reconstruction during the 2 year follow-up period were recorded. Revision was used as a marker for graft failure. The relationship between graft size and patient-reported outcomes was determined by multiple linear regression. The relationship between graft size and risk of revision was determined by dichotomizing graft size at 8mm and stratifying by age. RESULTS: After controlling for age, sex, operative side, surgeon, BMI, graft choice, and femoral tunnel drilling technique, a 1 mm increased in graft size was noted to correlate with 3.3-point increase in the KOOS-pain subscale (p = 0.003), a 2.0-point increased in the KOOS activities of daily living subscale (p = 0.034), a 5.2-point increase in the KOOS-sport/recreation function subscale (p = 0.004), and a 3.4-point increase in the subjective IKDC score (p = 0.026). Revision was required in 0 of 64 patients (0.0%) with grafts greater than 8mm in diameter and 14 of 199 patients (7.0%) with 8 mm or smaller grafts (p = 0.037). Among patients age 18 and under, revision was required in 0 of 14 patients (0.0%) with grafts greater than 8mm in diameter and 13 of 71 patients (18.3 %) with 8 mm or smaller grafts. CONCLUSIONS: Smaller hamstring autograft size is a predictor of poorer KOOS Sport and Recreation function 2 years following primary ACL reconstruction. Larger sample size is required to confirm the relationship between graft size and risk of revision ACL reconstruction. LEVEL OF EVIDENCE: Level 3